Preparation and Application of Solid, Salt‐Stabilized Zinc Amide Enolates with Enhanced Air and Moisture Stability. Issue 16 (22nd March 2017) - Chen, Yi‐Hung; Ellwart, Mario; Toupalas, Georgios; Ebe, Yusuke; Knochel, Paul
Abstract: The treatment of various N‐morpholino amides with TMPZnCl⋅LiCl (TMP=2, 2, 6, 6‐tetramethylpiperidyl) and Mg(OPiv)2 in THF at 25 °C provides solid zinc enolates with enhanced air and moisture stability ( t 1/2 in air: 1–3 h) after solvent evaporation. These enolates undergo Pd‐ and Cu‐catalyzed cross‐couplings with (hetero)aryl bromides as well as allylic and benzylic halides. The arylated N‐morpholino amides were converted into various ketones by LaCl3 ⋅2 LiCl mediated acylation with Grignard reagents. The new, solid enolates were used to prepare a potent anti‐breast‐cancer drug candidate in six steps and 23 % overall yield. Abstract : Solid chemistry : A convenient method for the preparation of solid zinc enolates with enhanced air and moisture stability is described. These enolates undergo Pd‐ and Cu‐catalyzed cross‐couplings. The reactive N ‐morpholino amides can be readily converted into aldehydes or various ketones. These new zinc enolates were employed in the short synthesis of a 3‐formylindole derivative that is a potent inhibitor of tubulin polymerization.